KEPEMIMPINAN KEPALA MADRASAH DALAM PEMBERDAYAAN SUMBER DAYA MANUSIA DI MA AL-MA’ARIF SINGOSARI PADA MASA PANDEMI COVID-19 - Wyeldan Bisri Habibi; Rosichin Mansur; Atika Z. Sufiyana (VICRATINA, 2021)
The leadership of the principal of madrasah is one of the factors that can encourage schools to be able to realize the vision, mission, goals and objectives of the school through planned programs. The purpose of this study was to determine the principal’s strategy in empowering human resources during the covid-19 period, the leadership of the principal in empowering human resources during the covid-19 period, and the supporting and inhibiting factors experienced by the principal in empowering human resources during the covid-19 period at MA Al-Ma’arif Singosari. This study used descriptive methods, and the data collection techniques are observation, interview, and documentation. Thus the subjects of this study were the principal, deputy head of curriculum, and MA Al-Ma’arif Singosari teachers. The data analysis was analyzed qualitatively. The result showed that: (1) The empowerment strategy includes giving encouragement, coaching and training activities, (2) leadership in empoerment includes fostering disclipine, leadership style, and responsiveness to environmental conditions, (3) The supprting factors for this study are adequate facilities and the environment, while the obstacle of this research is that the commitment of a teacher during the covid-19 period is still low. Kata Kunci: Principal Leadership, Empowering Human Resources, The Covid-19 Period